Datenqualität in der medizinischen Forschung Leitlinie zum adaptiven Management von Datenqualität in Kohortenstudien und Registern - Nonnemacher, Michael (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2014)
The benefit of cohort studies and registers in patient-oriented collaborative research depends largely on the quality of the data recorded there. Supply and quality research depend on scientifically proven methods and procedures to ensure high data quality. This guideline contains corresponding recommendations for the management of data quality in registers, cohort studies and data repositories. In the second edition, a significantly expanded set of indicators is provided and the use of the indicators is described as an example for different types of empirical research projects. The guideline is rounded off by a current literature review and analysis. It is therefore an important part of the range of measures to improve and ensure data quality in medical research.